Evaluation of pseudorabies virus glycoprotein gp50 as a vaccine for Aujeszky's disease in mice and swine: expression by vaccinia virus and Chinese hamster ovary cells. - Marchioli, C C (1987)
Pseudorabies virus (PRV) is an alphaherpesvirus which causes an economically important disease of swine. One of the PRV glycoproteins, gp50, was previously identified as the sequence homolog of herpes simplex virus glycoprotein gD (E.A. Petrovskis, J.G. Timmins, M.A. Armentrout, C.C. Marchioli, R.J. Yancey, Jr., and L.E. Post, J. Virol. 59:216-223, 1986). gp50 was evaluated as a PRV subunit vaccine candidate. gp50 protected mice from PRV-induced mortality either when delivered via infection with a recombinant vaccinia virus or when administered as a subunit vaccine produced in a eucaryotic cell line, Chinese hamster ovary (CHO) cells. In addition, gp50 synthesized in CHO cells protected pigs from lethal infection with PRV. This result demonstrates that a single viral glycoprotein could induce a protective immune response in the natural host of a herpesvirus infection.